Estudio de resistencia mecánica entre hormigón con fibra de coco y cascajo de ladrillo reciclado, y hormigón liviano - Cárdenas Salinas, Ulises Sebastian (2025)
The research aimed to compare the compressive strength of traditional lightweight concrete with that of a lightweight concrete to which alternative materials such as coconut fiber and recycled brick gravel were added, partially replacing cement and coarse aggregate, respectively. Four different dosages were developed: one was the traditional one, and the other three corresponded to the percentages of replacement with alternative materials. Cylinders were manufactured and subjected to compression tests at ages of 7, 14, and 28 days. The results showed that the traditional concrete exhibited greater compressive strength compared to the dosages with alternative materials. However, it was identified that some cylinders from the first batch exceeded the minimum strength of 140 kg/cm2, and even surpassed the strength of the cylinders from the traditional batch. It is noteworthy that the batch with replacement percentages of 0.5% coconut fiber and 6% recycled brick gravel achieved favorable results at both 14 and 28 days............